2003
DOI: 10.1055/s-2003-37193
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, Subjective and Performance Effects of Pseudoephedrine and Phenylpropanolamine During Endurance Running Exercise

Abstract: The aim of the study was to assess the effect of maximal therapeutic dosing of sympathomimetic amines found in over-the-counter (OTC) decongestant preparations on endurance running. Following familiarisation and a graded exercise test to determine maximal oxygen uptake (VO2 max), trained male runners (n = 8) completed four exercise sessions each separated by a minimum of one week. Each session was comprised of 20 min of sub-maximal treadmill running (70 % VO2 max) followed by a 5,000-m time trial on the treadm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
30
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 17 publications
6
30
2
1
Order By: Relevance
“…Of interest was the reduction in SBP in both tests with PSE use; an acute, but unexpected effect. This is contrary to a similar study by Chester et al, [4] which did not show a significant change in SBP or DBP during endurance running, even with use of a higher treatment dose of PSE (240 mg). Similarly, Hunter et al [16] reported no influence on performance in a cycling time trial with the use of 120 mg of PSE 2 hours prior to testing.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Of interest was the reduction in SBP in both tests with PSE use; an acute, but unexpected effect. This is contrary to a similar study by Chester et al, [4] which did not show a significant change in SBP or DBP during endurance running, even with use of a higher treatment dose of PSE (240 mg). Similarly, Hunter et al [16] reported no influence on performance in a cycling time trial with the use of 120 mg of PSE 2 hours prior to testing.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, the greatest effect size was observed in DBP during the 50 m sprint, but the magnitude of this effect was almost certainly trivial (99%). The results of our study support that therapeutic PSE use does not convey quantifiable benefits during explosive anaerobic events, although the sporting discipline of our study differed from that of the aforementioned, which utilised either prolonged [16] or endurance [4] testing protocols. Likewise, enhancement of performance was not evident in endurance events in our study.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In these studies, PSE doses of 60-120 mg resulted in urine concentrations of 30-200 μg·ml -1 (Chester et al, 2003;Gillies et al, 1996), underscoring a wide individual variation in its metabolism and excretion. Alternatively, with doses of ≥180 mg, exercise performance may be enhanced during 30 s maximal cycling (Gill et al, 2000), 1,500-m track running (Hodges et al, 2006), and ~30 min cycling time-trials (Pritchard-Peschek et al, 2010).…”
mentioning
confidence: 89%
“…Research investigating the influence of PSE on exercise performance suggests that any ergogenic effect does not manifest when taken in medicinal doses (≤120 mg) during submaximal and maximal running or during maximal strength activities (Chester et al,, 2003;Chu et al, 2002). In these studies, PSE doses of 60-120 mg resulted in urine concentrations of 30-200 μg·ml -1 (Chester et al, 2003;Gillies et al, 1996), underscoring a wide individual variation in its metabolism and excretion.…”
mentioning
confidence: 98%